2016
DOI: 10.1186/s40644-016-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of locoregional invasiveness of small-sized non-small cell lung cancers by enhanced dual-energy computed tomography

Abstract: BackgroundTo investigate the correlation between iodine-related attenuation of dual-energy computed tomography (DE-CT) and the histopathological invasiveness of surgically resected primary non-small cell lung cancers (NSCLCs) ≤ 3 cm in diameter.MethodsWe selected 63 consecutive NSCLC lesions from 60 patients (32 males, 28 females; age range, 39–85 years; mean age, 68 years). After injection of iodinated contrast media, arterial phases were scanned using 140-kVp and 80-kVp tube voltages. Three-dimensional iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…In CT, the assessment of the muscular system regarding metastatic lesions is severely hampered by different factors: the skeletal muscles constitute a large volume to investigate and usually show high attenuation so that iso- and moderately hyperattenuating metastases may get obscured. In the past, dual energy CT (DECT)-derived reconstructions highlighting the iodine signal have been shown to increase contrast and improve depiction of malignant lesions such as liver metastases, hepatocellular carcinoma, pancreatic or lung tumors [2429]. This can be achieved using iodine-specific maps or lower-energetic virtual monochromatic images which result in a higher x-ray absorption of iodine as the energy level is moved closer to its absorption maximum, the k-edge (33.2 keV) [30].…”
Section: Discussionmentioning
confidence: 99%
“…In CT, the assessment of the muscular system regarding metastatic lesions is severely hampered by different factors: the skeletal muscles constitute a large volume to investigate and usually show high attenuation so that iso- and moderately hyperattenuating metastases may get obscured. In the past, dual energy CT (DECT)-derived reconstructions highlighting the iodine signal have been shown to increase contrast and improve depiction of malignant lesions such as liver metastases, hepatocellular carcinoma, pancreatic or lung tumors [2429]. This can be achieved using iodine-specific maps or lower-energetic virtual monochromatic images which result in a higher x-ray absorption of iodine as the energy level is moved closer to its absorption maximum, the k-edge (33.2 keV) [30].…”
Section: Discussionmentioning
confidence: 99%
“…These can effectively inhibit the proliferation of tumor blood vessels and reduce the blood supply in the cancer area, then reduce the uptake of iodine by tumor cells. Vascular IC can reflect the efficacy of CMT drugs within the tissue [ 16 , 19 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the results of a study of 60 patients with 63 non-small cell lung cancers showed that volumetric iodine attenuation measurements in the primary lesion that were obtained with dual-energy CT were actually significantly lower in poorly differentiated tumors, compared with those in well-differentiated tumors (60). Iodine attenuation was also negatively correlated with local-regional invasiveness in the findings from this study (60). As a biomarker, iodine attenuation has also been investigated in the differentiation of metastatic and nonmetastatic mediastinal lymph nodes in non-small cell lung cancer.…”
Section: Cardiovascular Risk Screeningmentioning
confidence: 82%
“…In patients with established lung cancer, iodine quantification with dual-energy CT showed a moderate positive correlation (r = 0.51) with metabolic activity (ie, fluorine 18 fluorodeoxyglucose uptake) in both the primary lesion and in metastatic lymph nodes (59). In contrast, the results of a study of 60 patients with 63 non-small cell lung cancers showed that volumetric iodine attenuation measurements in the primary lesion that were obtained with dual-energy CT were actually significantly lower in poorly differentiated tumors, compared with those in well-differentiated tumors (60). Iodine attenuation was also negatively correlated with local-regional invasiveness in the findings from this study (60).…”
Section: Cardiovascular Risk Screeningmentioning
confidence: 95%